Team work indicator¨s of baseball five in the first world championship 2022 (Original) (Revista científica Olimpia, 2024)
The objective of this research is to analyze the behavior of teamwork indicators in the Cuban team in the First Five World Baseball Championship. carried out in Mexico at the end of 2022. Among other tools, to fulfill this purpose, the teamwork questionnaire is used by (Cañizares, 2022), the interview methods were used, with the coach and the teamwork questionnaire for the players. For data analysis, descriptive statistics were used: percentage, mean and median, and Sperman 's Correlation Coefficient. Data were processed using the Statistical Package for Social Sciences (SSPS) version 20.0 for Windows. As results, it is concluded that the significant role of teamwork was determined during the victory of the Cuba team in the First Five World Baseball Championship in 2022, evidencing that its indicators correlated significantly (highly), which contributed to high results in group efficiency.
Keywords: teamwork; baseball five; communication; cooperation; cohesion